A study on the procedures and conditions of polygamy application in federal territories / Hazwanis Hassan...[et al.] - Hassan, Hazwanis; Maarof, Ida Maslinda; Mohd Nazari, Farahah (2007)
This research focuses on two main issues in Federal Territories namely the procedure which requires consent of the existing wife in polygamous marriage and the other one is concerning conditions in section 23(4) and how the courts interpret each condition. The wording of this section shows that the consent of the existing wife is not mandatory because the section does not say that the husband must get the consent from the existing wife; instead he only needs to state whether he has obtained the consent or views or not. A big question arises as to why the consent of the existing wife is not required in the polygamy procedures. Thus, this research is conducted in order to study the necessity of the procedure which requires consent of the existing wife in an application for polygamy. The opinions from those who have the experience in handling polygamy cases are sought and decided cases that are relevant for the topic have also been included in this research. Other than the issue of consent, there is also detail discussions on how the courts determine whether the husband fulfills all the conditions stated in Section 23(4)(a) until (d). This issue is chosen because there is still no detail information as to how the courts interpret each condition in Section 23(4). For instance there is no suffice information what does the words "just and necessary" mean. So, this research is basically a study on the procedures and conditions of polygamy applications